A Seed-Specific Regulator of Triterpene Saponin Biosynthesis in Medicago truncatula. Issue 6 (17th April 2020) - Ribeiro, Bianca; Lacchini, Elia; Bicalho, Keylla U.; Mertens, Jan; Arendt, Philipp; Vanden Bossche, Robin; Calegario, Gabriela; Gryffroy, Lore; Ceulemans, Evi; Buitink, Julia; Goossens, Alain; Pollier, Jacob
Abstract : The discovery of a seed-specific regulator of hemolytic saponin biosynthesis in Medicago truncatula led to the identification of the missing P450 in the biosynthetic branch of these plant defense compounds. Abstract: Plants produce a vast array of defense compounds to protect themselves from pathogen attack or herbivore predation. Saponins are a specific class of defense compounds comprising bioactive glycosides with a steroidal or triterpenoid aglycone backbone. The model legume Medicago truncatula synthesizes two types of saponins, hemolytic saponins and nonhemolytic soyasaponins, which accumulate as specific blends in different plant organs. Here, we report the identification of the seed-specific transcription factor TRITERPENE SAPONIN ACTIVATION REGULATOR3 (TSAR3), which controls hemolytic saponin biosynthesis in developing M. truncatula seeds. Analysis of genes that are coexpressed with TSAR3 in transcriptome data sets from developing M. truncatula seeds led to the identification of CYP88A13, a cytochrome P450 that catalyzes the C-16α hydroxylation of medicagenic acid toward zanhic acid, the final oxidation step of the hemolytic saponin biosynthesis branch in M. truncatula . In addition, two uridine diphosphate glycosyltransferases, UGT73F18 and UGT73F19, which glucosylate hemolytic sapogenins at the C-3 position, were identified. The genes encoding the identified biosynthetic enzymes are present in clusters of duplicated genes in the M. truncatula genome. This appears to be a common theme among saponin biosynthesis genes, especially glycosyltransferases, and may be the driving force of the metabolic evolution of saponins.